(3GdXGgQs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3bO SHb bHd cJGHfG gPG CQHY hKdGKhf cJGHkG ai GdMjhGf hGdfHGJ hGdCMLGQ s
(3BNQgG (B:s
(3agPG HQgGf Ydi Pdc hSCPcQ eG gh Cbhi ef gPG ai ehGVYg Ef TGA Gddg s
(3Vef eLehY , JQJjHgG (B: 35s
(3hQO cPdc ai Qbes
(3hgh GdebGdI GdNGeSI hGdKdGKhf ef cJGH GdSHYjfs
(3SjJcQQ GSe gPG GdcJGH ai GdcJGH GdJGdi hgh ZjQgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs